Exploring the Contribution of Islam towards Global Governance Locating Ethics within the Discourse of Policy - Siyech, Mohammed Sinan (President University, 2017)
This paper aims to tackle the problem that Global Governance is currently encountering: the absence of ethics within the framework of policy making. It seeks to fill this gap by discussing how Islamic thought can contribute positively towards the making the notion of ethics central in governance. The paper will begin with an overview of Global Governance and the historical and current intellectual trends within this field. It will then provide an overview of the knowledge gaps that currently exist in global governance. From there, the paper will discuss the role of ethics in directing governance across the world. To do so, it will explore the literature on International Relations and Religion that critiques Max Weber’s ‘Secularization Thesis’. The paper then takes forward the discussion of Islam in international relations by examining the ethical principles that underpin the design of Islamic law. This is known as ‘Objectives of Islamic Law’ (‘Maqasid ash Shariah’). It then uses these principles to understand how Islam can contribute to two major aspects of global governance: (1) the environment and (2) human mobility specifically focused on refugees.